PROGRAMMABLE PERIPHERAL INTERFACE CONTROLLER AS A PORTAL TO 8255A PARKING - Slamet Darmanto; Luyung Dinaini. Skom. MMSi (Jurnal Sistem Komputer, 2002)
This portal is very helpful in dealing with vehicle parking attendants who will beentering, so the flow of vehicles going more smoothly. Thumbnail Portal uses steppermotors for each 7.2 degrees of rotation.For the provision of data from computer to the portal interface is needed betweenthem. In this case the authors use the Programmable Peripheral Interface 8255A. Thisinterface is very flexible so it can be used for simple interfacing to complex projectthough.